Scenes of Instruction, Scenes of Seduction: Figurations of Adolescence on the Late Twentieth-Century Stage. - Salvi, Carolyn. (2017)
Abstract: This dissertation seeks to trouble our culture's overvaluation of innocence by exploring the literary consequences of theatrical situations in which the scene of seduction and the scene of instruction are presumed to be one and the same. Because the adolescent stands in between the more actively theorized positions of child and adult, partaking of characteristics of both but not fully either, the adolescent crystallizes our cultural anxieties about what it means to pass on culture linguistically, morally, aesthetically, and politically. By focusing on the figure of the adolescent as the proto-citizen I am able to investigate the degree to which the overvaluation of innocence is connected to a desire to deny possibilities for radical social transformation. Chapter 1 reads Tom Stoppard's play Arcadia in order to establish norms of discourse around adolescence: more specifically investigating how the text participates in fetishization of the child figure in order to stave off the threat of the teenager's uncanny knowledge. Ahapter 2 uses Peter Shaffer's play Equus to map out the widespread influence of Freud's legacy on our modern conceptions of adolescence and adolescent sexuality, exploring how deviant sexuality is constructed as a potent threat the social order which dangerously reduces the adolescent's ability to take their place in the machinery of citizenship. While my first two chapters delineate the rhetorical tactics used to keep adolescents from achieving full citizenship, my second two chapters explore what happens when youth act as citizens anyway, disregarding their structural disenfranchisement in attempts to remake the civic sphere. Chapter 3 contrasts the different models of citizenship articulated by Arthur Miller's The Crucible and Paula Vogel's How I Learned to Drive. Drawing heavily on Lauren Berlant's theories of infantile and diva citizenship I argue that these plays investigate the relationship of private trauma to public embodiment, reframing the relationship between intellectual and sexual knowledge as the capacity to successfully enter into critical consciousness. Chapter 4 gives a reading of the film The City of Lost Children to demonstrate how a reimagining of the child and adolescent through aesthetics rather than ideology can support the development of new epistemologies.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of English.; Advisors: Joseph Litvak, and Martin Harries.; Committee: Judith Haber, and Radiclani Clytus.; Keywords: Theater, Performing arts, and Literature.